A note on the activity and species composition of sesiids [Lepidoptera: Sesiidae] as measured by pheromone traps and trunk sampling in apple orchards of southwestern Quebec - Chouinard, Gérald; Bellerose, Sylvie; Roy, Michèle; Vincent, Charles (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2006)
AbstractAdult males and larvae of sesiids were monitored in ten (1989–1991), five (2000) and two (2004) Quebec apple orchards. Multi Pher III traps baited with 99.1% Z, Z-3, 13-octadecadienyl acetate and 0.9% Z, E plus E, Z-3, 13-octadecadienyl acetate were used for adults, and trunk sampling was used for larvae. Synanthedon scitula, S. pyri, Podosesia syringae, S. acerrubri, S. fulvipes, S. exitiosa, S. acerni and Sesia tibialis males were captured between 1989 and 1991. Only 5 of the 347 adults of the S. scitula/pyri complex captured in 2000 belonged to S. pyri.